The Legacy of Edward Herman - Tom Mills (Media Theory)
This article reflects on the legacy of the American media critic and political economist Edward Herman; his influence on the field of media scholarship, and on the author’s own work. Its notes that Herman’s contribution has often been underappreciated due to Chomsky’s enormous stature as a public intellectual, and argues that as the principal author of the ‘propaganda model’ Herman made a significant contribution to scholarly and public understanding of the private news media. It notes a number of weaknesses in Manufacturing Consent, some of which are well known and have been addressed by the authors: an overemphasis on ‘closure’ and homogeneity in media systems, and a related ‘media centrism’ that may engender a certain political fatalism; an underdeveloped conception of the role of ideology; and a lack of empirical evidence on the operation of the five ‘filters’ as casual mechanisms giving rise to media content. It concludes that such weaknesses notwithstanding, Herman’s model is an exemplary piece of sociological theorising, and is only deterministic or simplistic insofar as it is ambitious and schematic.